An important role of l‐fucose biosynthesis and protein fucosylation genes in Arabidopsis immunity. Issue 2 (23rd January 2019) - Zhang, Li; Paasch, Bradley C.; Chen, Jin; Day, Brad; He, Sheng Yang
Summary: Plants mount coordinated immune responses to defend themselves against pathogens. However, the cellular components required for plant immunity are not fully understood. The jasmonate‐mimicking coronatine (COR) toxin produced by Pseudomonas syringae pv. tomato ( Pst ) DC3000 functions to overcome plant immunity. We previously isolated eight Arabidopsis ( scord ) mutants that exhibit increased susceptibility to a COR‐deficient mutant of Pst DC3000. Among them, the scord6 mutant exhibits defects both in stomatal closure response and in restricting bacterial multiplication inside the apoplast. However, the identity of SCORD6 remained elusive. In this study, we aim to identify the SCORD6 gene. We identified SCORD6 via next‐generation sequencing and found it to be MURUS1 ( MUR1 ), which is involved in the biosynthesis of GDP‐l ‐fucose. Discovery of SCORD6 as MUR1 led to a series of experiments that revealed a multi‐faceted role of l ‐fucose biosynthesis in stomatal and apoplastic defenses as well as in pattern‐triggered immunity and effector‐triggered immunity, including glycosylation of pattern‐recognition receptors. Furthermore, compromised stomatal and/or apoplastic defenses were observed in mutants of several fucosyltransferases with specific substrates (e.g. O ‐glycan, N ‐glycan or the DELLA transcriptional repressors). Collectively, these results uncover a novel and broad role of l ‐fucose and protein fucosylation in plant immunity.